2013
DOI: 10.1007/978-3-642-41939-3_24
|View full text |Cite
|
Sign up to set email alerts
|

Robot Trajectory Planning Using OLP and Structured Light 3D Machine Vision

Abstract: Abstract. This paper proposes a new methodology for robotic offline programming (OLP) addressing the issue of automatic program generation directly from 3D CAD models and verification through online 3D reconstruction. Limitations of current OLP include manufacturing tolerances between CAD and workpieces and inaccuracies in workpiece placement and modelled work cell. These issues are addressed and demonstrated through surface scanning, registration, and global and local error estimation. The method allows the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…3D surface reconstruction was performed with our own software developed within the GMPR group [11,12,14]. The justification for introducing 3D reconstruction is that we can make use of a new set of metrics in terms of error measures and perceived quality of the 3D visualization to assess the quality of the compression/ decompression algorithms.…”
Section: Results For Structured Light Images and 3d Surfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…3D surface reconstruction was performed with our own software developed within the GMPR group [11,12,14]. The justification for introducing 3D reconstruction is that we can make use of a new set of metrics in terms of error measures and perceived quality of the 3D visualization to assess the quality of the compression/ decompression algorithms.…”
Section: Results For Structured Light Images and 3d Surfacesmentioning
confidence: 99%
“…This includes 3D reconstruction from structured light images, and 3D reconstruction from multiple viewpoint images. Previously, we have demonstrated that while geometry and connectivity of a 3D mesh can be tackled by several techniques such as high degree polynomial interpolation [10] or partial differential equations [11,12], the issue of efficient compression of 2D images both for 3D reconstruction and texture mapping has not yet been addressed in a satisfactory manner. Moreover, in most applications that share common data, it is necessary to transmit 3D models over the Internet.…”
Section: Introductionmentioning
confidence: 99%
“…The software was develop within the GMPR group [135]at Sheffield Hallam University. The patterns of stripes are projected on the surface on an object and captured by a high resolution camera.…”
Section: Experimental Results In 2d and 3dmentioning
confidence: 99%
“…This includes 3D reconstruction from structured light images, and 3D reconstruction from multiple viewpoint images. In previous publications, we have argued that while geometry and connectivity of a 3D mesh can be tackled by several techniques such as high degree polynomial interpolation [114] or partial differential equations [125,135], the issue of efficient compression of 2D images both for 3D reconstruction and texture mapping has not yet been addressed in a satisfactory manner. Using structured light techniques for 3D reconstruction, surface patches can be compressed as a 2D image together with 3D calibration parameters, transmitted over a network and remotely reconstructed (geometry, connectivity and texture map) at the receiving end with the same resolution as the original data [133,136].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation